Firm quality and stock returns: Evidence from India. Issue 3 (3rd July 2021) - Sehgal, Sanjay; Pandey, Asheesh
ABSTRACT: Using data for 1 848 companies, we find that quality increases, not quality, drive stock returns in India. Profitability and safety seem to be relevant attributes for measuring quality. Our cross-sectional tests show that the role of quality in predicting returns is partially subsumed by momentum in short holding periods. Rational sources are not able to explain quality premiums. We find that quality premiums result from investor overreaction. At the same time, momentum profits are an outcome of investor underreaction, suggesting that investors pay more attention to fundamentals than past price trends. High investments by institutional investing may account for such behaviour.